PUBLIC PRIVATE PARTNERSHIP DALAM PENGEMBANGAN POTENSI WISATA DI KABUPATEN KUANTAN SINGINGI TAHUN 2011-2015 - Muhammad Ikram; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Not yet optimal performance of local government of KuantanSingingi Regency in running the concept of Public Private Partnership in tourism development and the failure of local government of KuantanSingingi Regency in encouraging investors to join in development of tourism area and government unable to utilize local media / national as a means to tourism promotion in KuantanSingingi Regency. Therefore, it is then that underlie the author to find out more and intend to conduct research on Public Private Partnership in the Development of Tourism Potential in KuantanSingingi Regency In the period 2011-2015.What factors affect the Public Private Partnership in the development of tourism potential in KuantanSingingiRegency. The purpose of the research is to know the Public Private Partnership in the development of tourism potential in KuantanSingingi Regency. Qualitative research methods. This research was conducted in KuantanSingingi Regency. Data sources are primary through interviews as well as secondary data sources. Data analysis technique is carried out with qualitative descriptive analysis. Currently KuantanSingingi District Government has not implemented the concept of Public Private Partnership in developing and managing tourism sector in KuantanSingingi regency. Inadequate management of facilities and infrastructure resulting in a lack of visiting tourists.Promotion made by the Department of Tourism and Culture KuantanSingingi regency about tourism events “pacujalur” and other tourist objects that have not been optimal, and the lack of socialization from the Department of Tourism and culture KuantanSingingi district to the community about the culture and traditions that exist in KuantanSingingi, Strategy DinasKebudayaan Tourism Youth and Sports KuantanSinginggi regency has not been done properly, This we can see from some existing strategies such as improving facilities and infrastructure both principal and supporting, direct or indirect promotion and work with the community, Of the three strategies there is no implemented maximally, very less in the implementation.Keywords: Public Private Partnership and Tourism